Numerical evaluation of complex permittivity of silicone rubber based on Jonscher's law. Issue 5 (2nd March 2020) - Yang, Zhenyu; Ito, Seitaro; Hirai, Naoshi; Ohki, Yoshimichi
Abstract : In this work, the two parts of complex permittivity in the frequency range 1–10 4 Hz were measured for sheet‐shaped samples of silicone rubber under various aging conditions. After that, fitting equations based on Jonscher's law were used to evaluate both the parts. As a result, it is clearly indicated that the fitting parameters in the equation of ϵ r ″ are linearly correlated with those in the equation of ϵ r ″ . This indicates that common information is contained in both ϵ r ′ and ϵ r ″ . A possible mechanism is also proposed to explain this phenomenon. © 2020 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.